2011
DOI: 10.1016/j.yexcr.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Visualization by BiFC of different C/EBPβ dimers and their interaction with HP1α reveals a differential subnuclear distribution of complexes in living cells

Abstract: How the co-ordinated events of gene activation and silencing during cellular differentiation are influenced by spatial organization of the cell nucleus is still poorly understood. Little is known about the molecular mechanisms controlling subnuclear distribution of transcription factors, and their interplay with nuclear proteins that shape chromatin structure. Here we show that C/EBPβ not only associates with pericentromeric heterochromatin but also interacts with the nucleoskeleton upon induction of adipocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 64 publications
2
35
0
Order By: Relevance
“…38 While C/EBPα and β share overlapping roles in the regulation of genes involved in energy metabolism, these isoforms have markedly different roles in the control of cellular differentiation and proliferation. The different roles of these BZip family proteins are reflected in the lack of sequence homology in their amino-terminal transactivation domains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 While C/EBPα and β share overlapping roles in the regulation of genes involved in energy metabolism, these isoforms have markedly different roles in the control of cellular differentiation and proliferation. The different roles of these BZip family proteins are reflected in the lack of sequence homology in their amino-terminal transactivation domains.…”
Section: Discussionmentioning
confidence: 99%
“…11 The earlier bimolecular fluorescence complementation study showed that the CD and the hinge region of HP1α could interact with the basic region of C/EBPβ. 38 This prompted us to focus our studies on the BZIP domain of C/EBPα.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin Immunoprecipitation (ChIP)-ChIP was performed following a modification of a previously described method (35). Briefly, proteins and DNA were cross-linked after HEK 293-T cell treatment with 1% formaldehyde for 10 min at 37°C and neutralized with glycine added at a final concentration of 0.125 M. Cells were rinsed twice with cold PBS, scraped, and centrifuged at 800 ϫ g for 5 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…This nuclear relocalization is blocked by MAPK inhibitors (Piwien Pilipuk et al 2003) and by carnosine (Gaya et al 2013). Using bimolecular fluorescence complementation in living cells, it was observed that LAP homodimers localize in euchromatin and heterochromatin whereas LIP homodimers localize exclusively in heterochromatin (Susperreguy et al 2011). Subnuclear relocalization of C/EBPβ has also been reported in macrophages ) and endothelial cells ) but it has been much less characterized.…”
Section: C/ebpβmentioning
confidence: 99%